2014
DOI: 10.1016/j.pacs.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of photoacoustic microscopy

Abstract: Building on its high spatial resolution, deep penetration depth and excellent image contrast, 3D photoacoustic microscopy (PAM) has grown tremendously since its first publication in 2005. Integrating optical excitation and acoustic detection, PAM has broken through both the optical diffusion and optical diffraction limits. PAM has 100% relative sensitivity to optical absorption (i.e., a given percentage change in the optical absorption coefficient yields the same percentage change in the photoacoustic amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
290
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(291 citation statements)
references
References 139 publications
(239 reference statements)
1
290
0
Order By: Relevance
“…with pulsed laser sources. In time-domain much larger photoacoustic pressures can be generated 2 . However, recently it was reported that frequency-domain PAM can achieve similar signal-to-noise ratios under the fulfillment of several requirements 3 .…”
Section: Introductionmentioning
confidence: 99%
“…with pulsed laser sources. In time-domain much larger photoacoustic pressures can be generated 2 . However, recently it was reported that frequency-domain PAM can achieve similar signal-to-noise ratios under the fulfillment of several requirements 3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, piezoelectric transducers have physical limitations. First, there is an inherent tradeoff between element size and signal-to-noise ratio (SNR) [1]. While large piezoelectric transducers in principle offer low thermal noise and high sensitivity, their surface shape must be well matched to the pressure wavefront to allow a high numerical aperture (NA) for photoacoustic microscopy (PAM) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…First, there is an inherent tradeoff between element size and signal-to-noise ratio (SNR) [1]. While large piezoelectric transducers in principle offer low thermal noise and high sensitivity, their surface shape must be well matched to the pressure wavefront to allow a high numerical aperture (NA) for photoacoustic microscopy (PAM) [1,2]. This can be achieved by employing focused transducers [3] or acoustic lenses [4]; however, both approaches limit the transducer's effective field of view (FOV) to the acoustic focal spot size, making mechanical scanning of the transducer necessary to cover the desired field of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage against other imaging modalities is simultaneously high spatial resolution, good contrast and a high penetration depth [3].…”
Section: Introductionmentioning
confidence: 99%